Thermal Changes of Root Surface of Anterior Primary Teeth in Pulpectomy with Er:YAG Laser - Zahra Bahrololoomi; Reza Birang; Nasim Chiniforush; Hazhir Yousefshahi; Elnaz Foroughi (Tehran University of Medical Sciences, 2018)
Objectives: Successful root treatment depends on elimination of microorganisms from the root canal. Considering incomplete removal of bacteria from the canal by usual methods, lasers have been suggested as a new modality. Despite their anti-bacterial properties, lasers can cause thermal changes. This study assessed the thermal changes of root surface in pulpectomy of primary teeth following the use of Er:YAG laser. Materials and Methods: Sixty primary anterior teeth were collected and prepared by K-file up to number 50. Then, they were randomly divided into two groups and were irradiated with Er:YAG laser. The first group was irradiated with 1 W laser and the second group with 1.5 W laser. The laser irradiation time was two 10-second cycles with a 2-second interval in both groups. Thermal changes were measured by a thermometer in the apical and coronal areas per second. The results were analyzed by repeated measures ANOVA considering the laser power as between-subject variable. Results: There was a temperature increase in the coronal and apical areas in use of 1 W power. There was a temperature rise in the coronal and apical areas in use of 1.5 W power. The temperature rise in the apical third was more than that in the coronal third; also, the average temperature rise was more in use of 1.5 W power than 1 W power. Conclusions: As the average temperature increase was not more than 7°C in any group, this type of laser seems to be suitable for root treatment of primary anterior teeth.